Cycling around Lysine Modifications. Issue 7 (July 2017) - Kumar, Surinder; Lombard, David B.
Abstract : Recent studies have revealed the existence of a plethora of previously unknown protein acyl-lysine modifications, affecting the functions of targets involved in diverse cellular processes. A recent study from the Hirschey laboratory has provided new chemical insights into the mechanisms of protein acylation.